DETERMINING THE RISK OF COMPLICATIONS AND BRONCHOSCOPY THROUGH THE MONITORING OF SYSTEMIC HEMODYNAMICS - G. A. Komarov; A. G. Korotkevich; Y. A. Churlyaev; P. G. Sitnikov (Неотложная медицинская помощь, 2016)
BACKGROUND. The appropriateness of the fibertracheobronchoscopy (FTBS) in patients with severe impaired consciousness, including with acute ischemic stroke (AIS), is still under debate. There is an ambiguous relation to FTBS performance.MATERIAL AND METHODS. Study of cardiac index (CI), systemic vascular index-grained resistance (ISSS), heart rate (HR), systolic, diastolic, mean arterial blood pressure (SBP, DBP, BP Wed), extravascular lung water (EVLW), gas exchange (oxygenation index (RaO2 /FiO2 ), were held from 1 to 7 days of the acute period of stroke by 40 patients before and after FTBS.RESULTS AND CONCLUSION. In both groups, SI, SBP, DBP, Wed Blood pressure, heart rate are increased. ISSS is decreased. Increased PaO2 /FiO2 , difference 27,61±4,9 mm pt.ct. Chronic and acute endobronchitis 1—2 degrees were revealed using endoscopy. Conducting FTBS reduced respiratory failure, PaO2 /FiO2 is increased. Heart failure is cause of deterioration after FTBS. Initially low C (less than 2,5 l/min/m2 ), high ISSS (3000 dyn·s·cm-5·m2 ) contraindication to FTBS.